2018
DOI: 10.1186/s12964-018-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy induced PRL3 expression promotes cancer growth via plasma membrane remodeling and specific alterations of caveolae-associated signaling

Abstract: BackgroundThe outcome of cancer therapy is greatly defined by the ability of a tumor cell to evade treatment and re-establish its bulk mass after medical interventions. Consequently, there is an urgent need for the characterization of molecules affecting tumor reoccurrence. The phosphatase of regenerating liver 3 (PRL3) protein was recently emerged among the targets that could affect such a phenomenon.MethodsThe expression induction of PRL3 in melanoma cells treated with chemotherapeutic agents was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Among the non-HGSOC cell lines both A2780 (i.e., endometrioid cancer) and A2780cp20 also had detectable PTP4A3 mRNA levels. PTP4A3 mRNA levels were higher in the drug resistant COV362-47R relative to the parental COV362 cells ( Figure 1 B) ( p < 0.05) consistent with the suggestion that drug resistance is associated with elevated PTP4A3 expression [ 26 ], although this did not appear to be translated into higher protein levels ( Figure 1 C and Supplementary Figure S2 ). HGSOC is considered to be intrinsically drug-resistant and of the HGSOC established cell lines, Kuramochi cells appeared to have the highest mRNA levels of all of the cells examined while OVCAR4 cells had the highest PTP4A3 protein levels ( Figure 1 C and Supplementary Figure S2 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Among the non-HGSOC cell lines both A2780 (i.e., endometrioid cancer) and A2780cp20 also had detectable PTP4A3 mRNA levels. PTP4A3 mRNA levels were higher in the drug resistant COV362-47R relative to the parental COV362 cells ( Figure 1 B) ( p < 0.05) consistent with the suggestion that drug resistance is associated with elevated PTP4A3 expression [ 26 ], although this did not appear to be translated into higher protein levels ( Figure 1 C and Supplementary Figure S2 ). HGSOC is considered to be intrinsically drug-resistant and of the HGSOC established cell lines, Kuramochi cells appeared to have the highest mRNA levels of all of the cells examined while OVCAR4 cells had the highest PTP4A3 protein levels ( Figure 1 C and Supplementary Figure S2 ).…”
Section: Resultssupporting
confidence: 85%
“…Unlike many other oncogenic proteins, PTP4A3 is rarely mutated; rather, the high protein levels result from gene amplification, increased transcription and translation, and possibly altered protein degradation [ 11 ]. It is noteworthy that PTP4A3 has been reported to be induced by genotoxic stress caused by cancer chemotherapeutic agents such as cisplatin, etoposide and doxorubicin [ 26 ]. We found that cell lines derived from HGSOC tumors express higher PTP4A3 mRNA levels than other histologic subtypes of OvCa or nonmalignant HIO-180 cells and had high PTP4A3 protein levels ( Figure 1 C).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PRL3 induces a stem cell-like transcriptional program in acute myeloid leukemia (AML) by upregulating LIN28B, a stem cell reprogramming factor 11 . More recently, PRL3 expression was induced upon genotoxic stress to promote cancer growth and survival 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported that BCAR1 and RAC1 also regulate cell movement and adhesion 36 . Specifically, RAC1-mediated cell migration is initiated by BCAR1 37 . Furthermore, the BCAR1/Rac1 axis can suppress colorectal cancer and metastasis through the Hippo, ERK, and PAK signaling pathways 38 , indicating the signaling pathway is indispensable in cell signal transduction.…”
Section: Discussionmentioning
confidence: 99%